Where Is This Tweet From? Inferring Home Locations of Twitter Users - Mahmud, Jalal; Nichols, Jeffrey; Drews, Clemens (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
We present a new algorithm for inferring the home locations of Twitter users at different granularities, such as city, state, or time zone, using the content of their tweets and their tweeting behavior. Unlike existing approaches, our algorithm uses an ensemble of statistical and heuristic classifiers to predict locations. We find that a hierarchical classification approach can improve prediction accuracy. Experimental evidence suggests that our algorithm works well in practice and outperforms the best existing algorithms for predicting the location of Twitter users.